Analysis of several loci from genome-wide association studies in Parkinson's disease in mainland China. (5th February 2015) - Liu, Zhen-hua; Guo, Ji-feng; Li, Kai; Wang, Ya-qin; Kang, Ji-feng; Wei, Yang; Sun, Qi-ying; Xu, Qian; Wang, Dan-ling; Xia, Kun; Yan, Xin-xiang; Xu, Chang-shui; et al.
Highlights: To investigate the association between several GWAS loci and sporadic PD in Chinese individuals. We find RAB7L1 rs708723 is associated with PD in Chinese population. GPNMB rs156429 polymorphism may be associated with male PD in Chinese individuals. NMD3 rs34016896 and STBD1 rs6812193 may not be associated with PD in Chinese Han population. Abstract: Large-scale meta-analyses of genome-wide association studies in Parkinson's disease (PD) have identified a number of susceptibility loci in sporadic PD. Since the characteristics of those loci in a Han Chinese population from mainland China were unknown, we performed a case-control replication study in this population and evaluated several single nucleotide polymorphisms (SNPs) identified in a recent GWAS-meta-analysis. In total, 933 subjects comprised of 460 PD patients and 473 controls were genotyped. We found strong evidence of an association for rs708723 in RAB7L1 in the total sample (genotype p = 0.01, allele p = 0.01, OR = 0.78, 95% CI = 0.65–0.94). With rs156429 in GPNMB, there was a significant difference in genotype and allele distribution between male PD patients and the control subgroup (genotype p = 0.01, allele p = 0.01, OR = 0.67, 95% CI = 0.49–0.92). However, we did not observe any significant difference in genotype or allele distribution between PD and control for rs34016896 in NMD3 and rs6812193 in STBD1.